Academic Senate Minutes 2006-02-23 - Academic Senate:::::::::
Agenda approved. Minutes of 2/9/06 with amendments approved. Faculty and SSP's Eligible for Emeritus Status approved. Preliminary Level I Education Specialist (ES-I) Credential Program in Mild/Moderate Disabilities and in Moderate/Severe Disabilities Revision approved. History Minor revision approved. Special Guest: Faculty Trustee Craig Smith. Special Report on the Green Music Center finances.